2014
DOI: 10.1111/clr.12442
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Bio‐Oss® grafted marginal gaps at implants placed into fresh extraction sockets of incisor teeth in dogs: a study on the effect of submerged vs. non‐submerged healing

Abstract: There was very little difference in healing outcomes as well as modelling of the facial bone wall between the submerged and NS protocols in relation to immediate implant placement in this dog model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 40 publications
(87 reference statements)
4
22
0
Order By: Relevance
“…Hence extraction could be carried out in a minimally traumatic manner. Secondly, Mellati et al () reported that the dimensions of the maxillary second incisor extraction socket were very similar to that seen in humans, with a mean width of 6mm and a mean depth of 11mm. Considering that implant placement and dimensional changes following extraction have critical importance in the anterior maxilla, the use of the maxillary second incisor provides a model with greater clinical relevance.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Hence extraction could be carried out in a minimally traumatic manner. Secondly, Mellati et al () reported that the dimensions of the maxillary second incisor extraction socket were very similar to that seen in humans, with a mean width of 6mm and a mean depth of 11mm. Considering that implant placement and dimensional changes following extraction have critical importance in the anterior maxilla, the use of the maxillary second incisor provides a model with greater clinical relevance.…”
Section: Discussionmentioning
confidence: 77%
“…While in implant and ridge preservation studies, the mandibular pre‐molar was seen as ideal due to the ability to extract it without damaging the socket walls. However, De Santis et al () successfully utilised the maxillary second incisors in Labradors to study immediate implants, which was more recently followed by Mellati et al (). Both these studies were able to highlight several advantages associated with the use of maxillary second incisors as an experimental model over the mandibular pre‐molar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, implants were loaded approximately 3 months after placement using the one‐stage surgical protocol, which may have affected the amount of CBL. The effect of single stage implant placement versus submerged healing has been previously investigated, showing comparable clinical and radiographic results . However, peri‐implant CBL has been demonstrated by others to be significantly higher in the submerged healing group .…”
Section: Discussionmentioning
confidence: 96%
“…) and 28.75% after 3 months (Mellati et al. ). This study is the first preclinical confirmation of the beneficial effects of contour augmentation combined with early implant placement on lateral bone augmentation to the authors’ knowledge.…”
Section: Discussionmentioning
confidence: 99%